Teacher Efforts in Overcoming Obstacles to History Learning in the Education Unit Level Curriculum at Madrasah Aliyah Al Irsyad Gajah Demak - Ardiansyah, Pradita (Indonesian Journal of History Education, 2017)
This article examines the implementation of the SBC, which puts more pressure on the ability of teachers to develop learning materials and requires the development of self-esteem after implementing the learning process because self-development is a significant component of the SBC. This study used qualitative research methods. The informant in this study is a history teacher. Data collection techniques in this study use several methods: (1) observation, (2) the interview, and (3) documentation. Analyzes were performed using interactive models. The results showed that several perceived barriers to MA Al Ershad, a history teacher in implementing the SBC Elephant, were still at the learning process level, not the curriculum level itself. Efforts are being made to overcome the obstacles teachers SBC is to intensify the PAIKEM approach.